The Determination of Applicable Law to Torts based on “the Law which is more closely connected” - Sibel Özel (Public and Private International Law Bulletin)
Legislations stipulate that the law applicable to torts is lex loci delicti commissi, i.e., the law of the place where the tort is committed. In the case that the law of the event leading to damage differs from the law of damage, then lex loci damni, or, the law of the place where damage occurred, is preferable. The application of the law of damage requires the definition and localization of damage. This article proposes a definition of damage and determines to which place damage occurs in terms of applicable laws to claims as a result of torts. Where the lex loci damni is remote or fortuitous, then this rule is displaced by the law more closely connected to the issue. Determining the law most closely connected to the issue should be based on a review of all factors that constitute the tort claim or the law applicable to the underlying relationship between parties connected to the tort.